Inflammatory immune profiles associated with disease severity in pulmonary tuberculosis patients with moderate to severe clinical TB or anemia - Ashenafi, Senait; Loreti, Marco Giulio; Bekele, Amsalu; Aseffa, Getachew; Amogne, Wondwossen; Kassa, Endale; Aderaye, Getachew; Brighenti, Susanna (Frontiers in Immunology, 2023)
As an expert in the field of tuberculosis (TB) immunology, I have been invited to contribute to the research topic "Innate and Adaptive Immunity against Tuberculosis Infection: Diagnostics, Vaccines, and Therapeutics". I submitted an abstract end of April 2023, whereafter I received an approval to continue with a full submission of a manuscript. Briefly, in this study we explored inflammatory immune profiles in pulmonary tuberculosis (TB) patients with different disease severity scores, using multiplex protein profiling including 64 inflammation markers and cytokines. A well-characterized clinical cohort of pulmonary TB patients (n=107) was enrolled in Addis Ababa, Ethiopia, where we have determined clinical disease severity using a previously validated composite TB symptoms score. We have also determined blood hemoglobin levels and the extent of lung disease using chest X-ray in this patient cohort. Ultimately, we test the immune profile in three different disease severity groups including: 1) mild vs moderate-severe TB disease, 2) anemic vs non-anemic TB, 3) limited vs extensive lung involvement. Healthy controls were also included for assessment of baseline levels of inflammatory mediators. To our knowledge, this is the first multiplex study investigating inflammatory mediators as biomarkers of TB disease severity and treatment prognosis.